The Myth of Electability: What It Really Takes for Women to Win - Cain, Emily (Maine Policy Review, 2019)
Drawing on her experience in the Maine Legislature and current role as executive director of EMILY’s List, in this Margaret Chase Smith Essay, Emily Cain shares insight into the myth of electability and examples of the important impact women have made over the past 35 years politically and how they have changed our political landscape along the way.